Existence Results for a System of Coupled Hybrid Fractional Differential Equations - Bashir Ahmad; Sotiris K. Ntouyas; Ahmed Alsaedi (The Scientific World Journal)
This paper studies the existence of solutions for a system of coupled hybrid fractional differential equations with Dirichlet boundary conditions. We make use of the standard tools of the fixed point theory to establish the main results. The existence and uniqueness result is elaborated with the aid of an example.